Development of Hybrid Learning Media Integrating Android and Web Platforms with an Adaptive Learning Approach - Renny Permata Saputri; Monica Fransisca (Universitas Negeri Semarang, 2026)
The increasing adoption of digital technology in education requires learning media that are flexible and capable of accommodating students’ diverse learning abilities. However, learning media used in vocational high schools often apply a uniform approach, limiting opportunities for personalized learning. This study aimed to develop hybrid learning media based on Android and web platforms using an adaptive learning approach for the Basic Programming course. The study employed a Research and Development (R&D) method with the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 36 eleventh-grade students from the Software Engineering and Informatics, Networking & Application Systems programs at a vocational high school in Padang, Indonesia. Data were collected through observations, interviews, expert validation questionnaires, and student response questionnaires. The results showed that the developed media achieved validity scores of 92.4% from media experts and 90.8% from subject matter experts, both categorized as highly valid. Student responses reached 89.7%, indicating a very positive acceptance level. The adaptive learning features enabled personalized delivery of learning materials and exercises based on students’ abilities. Therefore, the developed hybrid learning media is considered feasible and effective for supporting personalized learning in vocational education.